The value of sick pay - Adams-Prassl, A; Boneva, T.; Golin, M; Rauh, C (University of Oxford, 2021)
Not all countries provide universal access to publicly funded paid sick pay. Amongst countries that do, compensation rates can be low and coverage incomplete. This leaves a significant role for employer-provided paid sick pay in many countries. In this paper, we study who has access to employer-provided sick pay, how access to sick pay relates to labor supply when sick, and how much it is valued by workers for themselves and others. We find that workers in jobs with high contact to others are particularly unlikely to have employer provided sick pay, as are economically insecure workers who are least able to afford unpaid time off work. We find that workers without sick pay are more likely to work when experiencing cold-like symptoms and are less willing to expose themselves to health risks at work during the pandemic. Using vignettes, we reveal that large shares of workers have a very high, but even more have a very low willingness to sacrifice earnings for access to sick pay. Together our findings highlight the unequal distribution of access to sick pay and the potentially strong negative externalities of not providing it publicly. The pandemic may have made these issues more salient as perceived probabilities of having to self-isolate are positively related to support for publicly provided sick pay. Finally, we find that providing information on the health externality of paid sick leave increases support for the public provision of sick pay, suggesting that there might be a public under-provision because individuals do not factor in the externalities.